2019
DOI: 10.1115/1.4043643
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Study of Diesel-Piloted Natural Gas Direct Injection Under Different Operating Conditions

Abstract: Natural gas as an alternative fuel in engine applications substantially reduces both pollutant and greenhouse gas emissions. High pressure dual fuel (HPDF) direct injection of natural gas and diesel pilot has the potential to minimize methane slip from gas engines and increase the fuel flexibility, while retaining the high efficiency of a diesel engine. Speed and load variations as well as various strategies for emission reduction entail a wide range of different operating conditions. The influence of these op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Under an assumption that a maximized overlapping of diesel and gas jets after the auto-ignition of diesel fuel will yield the best performance, a converging injector configuration with small angle (a few degrees) was recommended [88]. The effect of the dual-fuel jet interaction under engine-relevant reactive conditions was studied by Fink et al [89,90] in a RCEM. Different injector orientations were used to change the degree of jet interaction-the gas injection angle was changed by rotating the injector while the diesel jet was fixed.…”
Section: Dual-fuel High Pressure Direct Injection Compression-ignitiomentioning
confidence: 99%
See 2 more Smart Citations
“…Under an assumption that a maximized overlapping of diesel and gas jets after the auto-ignition of diesel fuel will yield the best performance, a converging injector configuration with small angle (a few degrees) was recommended [88]. The effect of the dual-fuel jet interaction under engine-relevant reactive conditions was studied by Fink et al [89,90] in a RCEM. Different injector orientations were used to change the degree of jet interaction-the gas injection angle was changed by rotating the injector while the diesel jet was fixed.…”
Section: Dual-fuel High Pressure Direct Injection Compression-ignitiomentioning
confidence: 99%
“…Fink et al [90] investigated the effects of ambient pressure and temperature on dual-fuel combustion using shadowgraphy and OH-chemiluminescence in a RCEM. It was found that the ignition of gas jet becomes possible at a wider range of injector orientations and relative SOIs with an increasing ambient pressure and temperature (i.e., from 780 to 920 K).…”
Section: Dual-fuel High Pressure Direct Injection Compression-ignitiomentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the NG stratification, several studies have concluded that complex interactions between the NG jet and pilot jet and ignition are critical to PIDING combustion performance. 2729 Using a rapid compression-expansion machine (RCEM), Fink et al 28 demonstrated that for positive RIT where pilot ignition occurs undisturbed by the NG jet, a wide range of relative spray angles can be used to produce robust NG ignition. However, when there is temporal overlap of the pilot and NG jets (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In order to further understand the combustion process for HPDI engines, numerous efforts have been performed to investigate the effects of various injection and air-exchange strategies on the engine performance and emission characteristics. , The combustion process of HPDI engines is more complicated than traditional diesel and gasoline engines. To get better understanding of the combustion process, it is essential to well reveal the detailed in-cylinder combustion process. Optical diagnostics techniques have been playing a significant role in visualizing the engine flow, spray, combustion, and emission formation processes, which contributes to the development of fluid dynamics models (CFD) .…”
Section: Introductionmentioning
confidence: 99%